Hesperidin as a preventive resistance agent in MCF-7 breast cancer cells line resistance to doxorubicin - Rifki Febriansyah, M.Sc., Apt, Dyaningtyas Dewi Pamungkas, dkk (Fakultas Kedokteran UMY, 2014)
To evaluate of hesperidin to overcome resistance of doxorubicin in MCF-7 resistant doxorubicin cells (MCF-7/Dox) in cytotoxicity apoptosis and P-glycoprotein (Pgp) expression in combination with doxorubicin